Number of staff optimization of tollman scheduling with integer linear programming / Nurul Athirah Syuhadah Ruslan and Diana Sirmayunie Mohd Nasir - Ruslan, Nurul Athirah Syuhadah; Mohd Nasir, Diana Sirmayunie (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Scheduling problem is a great concern for several company. Larger organizations have to maintain proper scheduling of their employees to ensure good service. The schedule of toll booth collectors is one of the important elements of the company. Due to the rise of highways users, toll plaza has to make sure that they have enough workers manning the toll booths due to the increase in highways users in order to prevent any issues. They must take into consideration the staffing costs even if they can hire additional employees to make sure they do not run out of staff. Therefore, the purpose of this study was to determine optimum number of tollman working per day in order to minimize staffing costs. To achieve these objectives, Integer Linear Programming and LINGO Software were applied. The issue of too many or too few tollman will be reduced once the ideal number of tollman working has been reached. The cost of hiring new employees might be automatically decreased as a result. The data obtained those 30 workers needed per day for this company and the staffing costs per day is RM1800. Based on findings, it is recommended that a toll plaza needs a minimum of 15 tollman per day with staffing cost reduced to RM900 which has decreased staffing costs per day which still fulfil the company constraints.